Building ground for didactics in a patient decision aid for hip osteoarthritis. Exploring patient-related barriers and facilitators towards shared decision-making. Issue 7 (July 2020) - Brembo, Espen Andreas; Eide, Hilde; Lauritzen, Mirjam; van Dulmen, Sandra; Kasper, Jürgen
Abstract: Objective: The aim of the present study was to explore patient-related barriers and facilitators towards shared decision-making (SDM) during routine orthopedic outpatient consultations as part of the process of developing a patient decision aid (PDA) for patients with hip osteoarthritis (OA). Methods: Consultations comprising nineteen hip OA patients referred to an orthopedic surgeon for treatment decision-making were observed, audio recorded and transcribed. Iterative thematic analysis proceeded, based on a taxonomy of generic patient-related barriers towards SDM grounded in the Theory of Planned Behavior (TPB). Results: A targeted taxonomy provided a structured overview of 26 factors influencing hip OA patients' intention to engage in SDM. Patients' perceived ability to change the agenda of the visit emerged as seminal factor and was added to the generic taxonomy. Conclusion: Using a TPB-based taxonomy, we were able to identify and structure generic and context specific SDM barriers. Addressing patients' communication self-efficacy should be included as didactic feature in PDAs. Practice implications: PDAs for hip OA should be designed for the broad spectrum of decision-making support needs occurring throughout the continuum of the disease. The provided taxonomy may contribute as guidance within implementation strategies that aim to support patients' intentions to engage in SDM.